2014
DOI: 10.1038/mt.2013.212
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Antiviral Strategy for Targeting Hepatitis B Virus Genome Using Transcription Activator-Like Effector Nucleases

Abstract: The hepatitis B virus (HBV) is a DNA virus that can cause chronic hepatitis B (CHB) in humans. Current therapies for CHB infection are limited in efficacy and do not target the pre-existing viral genomic DNA, which are present in the nucleus as a covalently closed circular DNA (cccDNA) form. The transcription activator-like (TAL) effector nucleases (TALENs) are newly developed enzymes that can cleave sequence-specific DNA targets. Here, TALENs targeting the conserved regions of the viral genomic DNA among diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
107
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(111 citation statements)
references
References 48 publications
0
107
0
Order By: Relevance
“…Cleavage of the HBV DNA also reduced the number of circulating viral particles, indicating disruption of HBV replication. Later in 2013, these results were supported by Chen and colleagues [23], who also showed that TALENs designed to bind to the C and polymerase (P) open reading frames reduced viral antigen and pregenomic RNA expression in vitro and in vivo. They found that the antiviral effect was not limited to a single genotype, suggesting that a TALEN pair may be used to target multiple genotypes.…”
Section: Anti-hbv Talensmentioning
confidence: 89%
“…Cleavage of the HBV DNA also reduced the number of circulating viral particles, indicating disruption of HBV replication. Later in 2013, these results were supported by Chen and colleagues [23], who also showed that TALENs designed to bind to the C and polymerase (P) open reading frames reduced viral antigen and pregenomic RNA expression in vitro and in vivo. They found that the antiviral effect was not limited to a single genotype, suggesting that a TALEN pair may be used to target multiple genotypes.…”
Section: Anti-hbv Talensmentioning
confidence: 89%
“…Since this first study, numerous other groups have employed similar strategies to target HBV. The first follow-up studies showed antiviral activity in vitro by ZFNs delivered using adeno-associated virus (AAV) vectors (Weber et al 2014b), or by TALENs in vitro and in a mouse hydrodynamic injection model of HBV lacking cccDNA (Bloom et al 2013; Chen et al 2014). Importantly, the in vitro studies using TALENs showed for the first time that HBV cccDNA could be cleaved and disrupted directly.…”
Section: The Current Status Of Gene-editing Antiviral Therapiesmentioning
confidence: 99%
“…In addition, several genome editing technologies have been developed to silence sequencespecific cle avage of cccDNA. These include zinc finger nucleases (ZFNs) [100,101] , transcription activatorlike effector nucleases (TALENs) [102,103] , and the clustered regularly interspaced short palindromic repeat (CRISPR)/CRISPR associated system (Cas). These sequence-specific genome editing technologies could induce doublestranded breaks at certain DNA sites.…”
Section: Inhibition Of Hbv Replicationmentioning
confidence: 99%